2015
DOI: 10.1186/1471-2288-15-10
|View full text |Cite
|
Sign up to set email alerts
|

Impact of variability in adherence to HIV antiretroviral therapy on the immunovirological response and mortality

Abstract: BackgroundSeveral previous studies have shown relationships between adherence to HIV antiretroviral therapy (ART) and the viral load, the CD4 cell count, or mortality. However, the impact of variability in adherence to ART on the immunovirological response does not seem to have been investigated yet.MethodsMonthly adherence data (November 1999 to April 2009) from 317 HIV-1 infected patients enrolled in the Senegalese ART initiative were analyzed. Latent-class trajectory models were used to build typical trajec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 25 publications
1
18
1
1
Order By: Relevance
“…Respondents in the current study (44% (76)) were found to be non adherent to their prescribed cART (Figure 1). It must be emphasized that adherence to cART is critical for successful viral suppression because non adherence could lead to an increase in HIV viremia, risk of treatment failure, and accumulating resistance mutations [37]. The 44% non adherence rate is very alarming and Similar to the current study, in Thailand slightly higher (48.4%) suboptimal adherence to cART among adolescents was reported [24].…”
Section: Adherence To Cartsupporting
confidence: 67%
“…Respondents in the current study (44% (76)) were found to be non adherent to their prescribed cART (Figure 1). It must be emphasized that adherence to cART is critical for successful viral suppression because non adherence could lead to an increase in HIV viremia, risk of treatment failure, and accumulating resistance mutations [37]. The 44% non adherence rate is very alarming and Similar to the current study, in Thailand slightly higher (48.4%) suboptimal adherence to cART among adolescents was reported [24].…”
Section: Adherence To Cartsupporting
confidence: 67%
“…Adolescents and young adults globally pose challenges to HIV treatment programs, particularly in LMICs where weak health systems, lack of support for adherence and retention and limited access to VL monitoring, contribute to VF. 26,27 While ART has been effective in decreasing AIDS-related deaths among adults, benefits among adolescents and younger adults have been limited. 21 In SSA, poor adherence and loss to CD4 count (cells/mm 3 follow-up among adolescents and young adults have been reported compared to older individuals living with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…In general, research to date on medication non‐adherence has been disease‐specific, assessing the impact of suboptimal adherence on surrogate health outcomes such as blood pressure, cholesterol levels and biological response . As multimorbidity increases with age, a disease‐specific perspective may not be appropriate for older cohorts …”
Section: Introductionmentioning
confidence: 99%
“…8,9 In general, research to date on medication non-adherence has been disease-specific, assessing the impact of suboptimal adherence on surrogate health outcomes such as blood pressure, cholesterol levels and biological response. [10][11][12] As multimorbidity increases with age, a disease-specific perspective may not be appropriate for older cohorts. 13,14 In 2002, a meta-analysis of the influence of adherence on health outcomes concluded that adherent people were nearly 3 times more likely to experience a positive treatment outcome than non-adherent people.…”
Section: Introductionmentioning
confidence: 99%